What Touched Your Heart? Collaborative Story Analysis Emerging From an Apsáalooke Cultural Context. (July 2017) - Hallett, John; Held, Suzanne; McCormick, Alma Knows His Gun; Simonds, Vanessa; Real Bird, Sloane; Martin, Christine; Simpson, Colleen; Schure, Mark; Turnsplenty, Nicole; Trottier, Coleen
Community-based participatory research and decolonizing research share some recommendations for best practices for conducting research. One commonality is partnering on all stages of research; co-developing methods of data analysis is one stage with a deficit of partnering examples. We present a novel community-based and developed method for analyzing qualitative data within an Indigenous health study and explain incompatibilities of existing methods for our purposes and community needs. We describe how we explored available literature, received counsel from community Elders and experts in the field, and collaboratively developed a data analysis method consonant with community values. The method of analysis, in which interview/story remained intact, team members received story, made meaning through discussion, and generated a conceptual framework to inform intervention development, is detailed. We offer the development process and method as an example for researchers working with communities who want to keep stories intact during qualitative data analysis.